Hubungan Pengetahuan Basic Life Support terhadap Aplikasi dalam Menangani Kasus Kegawatdaruratan pada Tim BASARNAS - Ami Febriza Achmad; Sri Ayu Lestari Wulandari (Lembaga Layanan Pendidikan Tinggi (LL-DIKTI) Wilayah IX Sulawesi, 2020)
Abstract This study aims to determine the level of knowledge of the BASARNAS employees about Basic Life Support on the level of application in handling emergency cases. This research is an analytic study with cross sectional method. The study was conducted at the BASARNAS Office in Makassar by involving 65 BASARNAS employees as respondens. The level of knowledge about BLS and its application is measured by questionnaire. Bivariate analysis with Chi-Square test was used to see the relationship between the level of knowledge about BLS and the level of its application in handling emergency cases. There was a significant relationship between the level of knowledge of BLS BASARNAS employees and the level of application in handling emergency cases. The statistical test obtained the value of p = 0.001, indicating the relationship between the level of knowledge about BLS and the level of application in handling emergency cases.